Cultivo y pruebas de susceptibilidad para el bacilo de Koch en pacientes con tuberculosis pulmonar. - Tapia Alarcón, Jacquelin Fernanda (2024)
Tuberculosis is a pulmonary and extrapulmonary infection caused by Mycobacterium tuberculosis. It is considered one of the leading causes of death in the world, although it is a treatable and curable disease. This research was carried out by means of a bibliographic review, with the purpose of gathering scientific information on the culture and susceptibility tests of this mycobacterium. The present work is a descriptive, documentary and non-experimental, retrospective study, where 55 scientific articles were reviewed, selecting 23, by means of inclusion and exclusion criteria. The information was searched in databases such as Pubmed, Scielo, Google Books, Elsevier, MSP Manuals, PAHO, WHO, Dialnet, Biomedica, Medigraphic and Google Scholar. The analysis and discussion of different authors provided answers to the proposed objectives, demonstrating the most used susceptibility tests: Gene Xpert MTB/Rif, Gene Xpert MTB/Rif Ultra, Gene Xpert MTB/XDR, Genotype®MDRTBplus, Genoscholar TB-NTM+MDR and Genotype MTBDR sl. As for diagnostic methods for pulmonary tuberculosis, Xpert MTB/RIF and ULTRA, Xpert MTB/XDR, Genotype®MDRTBplus, Genoscholar TB-NTM+MDR, Genotype MTBDR sl were used, followed by conventional methods: culture media (solid or liquid) and Zhiel Neelsen staining. In conclusion, molecular biology techniques were applied more frequently for the isolation, sensitivity and resistance of the tubercle bacillus, leaving behind traditional methods, because they present high sensitivity and specificity, with fast results, helping to implement timely treatments for patients with pulmonary TB, avoiding the appearance of multidrug-resistant strains.